Granular catalyst for hydrolysis of aminonitriles and aminoamides to amino acids or their derivatives

JP2025505402APending Publication Date: 2025-02-26EVONIK OPERATIONS GMBH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024544509
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-28
Filing Date
2023-01-26
Publication Date
2025-02-26

Smart Images

  • Figure 2025505402000007
    Figure 2025505402000007
  • Figure 2025505402000008
    Figure 2025505402000008
  • Figure 2025505402000001
    Figure 2025505402000001
Patent Text Reader

Abstract

The present invention relates to a granular catalyst for the hydrolysis of aminonitriles and / or aminoamides to amino acids or derivatives thereof, to a process for preparing said catalyst, as well as to a process for preparing amino acids or derivatives thereof, comprising a step of contacting a solution or suspension comprising aminonitriles and / or aminoamides with water in the presence of the catalyst according to the invention and / or in the presence of a catalyst obtained by the process of the invention.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a granular catalyst for the hydrolysis of aminonitriles and / or aminoamides to amino acids or derivatives thereof, to a process for preparing said catalyst, as well as to a process for preparing amino acids or derivatives thereof, comprising a step of contacting a solution or suspension comprising aminonitriles and / or aminoamides with water in the presence of the catalyst according to the invention and / or in the presence of a catalyst obtained by the process of the invention.

[0002] Amino acids are fundamentally important for animal nutrition due to their function as protein building blocks for animal and human nutrition. Feed is therefore further enriched with amino acids such as D,L-methionine, thereby increasing its nutritional value. D,L-methionine is an essential amino acid that must be ingested with food. As a feed additive, D,L-methionine contributes to an efficient, healthy and environmentally friendly diet for livestock, especially poultry and pigs. D,L-methionine is therefore also a key building block with regard to the sustainable supply of animal protein to the growing world population. A cost-effective synthesis process for D,L-methionine, well suited for large-scale industry, is therefore of great importance.

[0003] On an industrial scale, methionine is produced chemically by the Bucherer-Bergs reaction. The Bucherer-Bergs reaction is a variant of the Strecker synthesis. The starting materials for this reaction are 3-methylmercaptopropionaldehyde (MMP), produced by the reaction of 2-propenal with methyl mercaptan, hydrogen cyanide, ammonia and carbon dioxide. The reaction of the starting materials gives 5-(2-methylmercaptoethyl)-hydantoin (methionine hydantoin), which is hydrolyzed to give methionate. The hydrolysis of methionine hydantoin requires harsh conditions and a stoichiometric amount of base, usually sodium hydroxide, potassium hydroxide or potassium carbonate. Thus, the hydrolysis of methionine hydantoin typically gives the sodium or potassium salt of methionine (sodium methionate or potassium methionate). According to known methods, methionine is released from sodium or potassium methionate by neutralizing the salt with sulfuric acid. The neutral methionine thus formed precipitates from the solution and can be easily filtered from the solution. The sodium or potassium sulfate produced as a by-product must be recycled or otherwise disposed of.

[0004] US Patent No. 5,770,769 discloses the so-called Degussa potassium carbonate recycle process, in which methionine is finally released from its potassium salt by treating the hydrolysate with carbon dioxide, and the methionine precipitate can be filtered from the mother liquor containing potassium carbonate and potassium bicarbonate. The latter can be recovered, but this requires a circuit containing large amounts of brine. Furthermore, the formation and hydrolysis of methionine hydantoin require harsh and energy-intensive conditions, e.g., temperatures of up to 200° C. for the hydrolysis of hydantoin. Thus, there remains a need for an industrially viable process that does not have these drawbacks at all or to a lesser extent.

[0005] One approach to circumvent the above drawbacks is to prepare methionine from 2-amino-4-(methylthio)butanenitrile (methionine nitrile; MMP aminonitrile; MMP-AN) via 2-amino-4-(methylthio)butanamide (methionine amide) in the presence of various metal oxide catalysts.

[0006] WO 2001 / 060788 discloses a general method for preparing methionine. In this method, methionine nitrile is prepared from 2-hydroxy-4-(methylthio)butanenitrile (MMP cyanohydrin, MMP-CN) and ammonia, and hydrolyzed with alkali hydroxide in the presence of acetone to obtain methionine amide, which is then further hydrolyzed with a titanium-containing catalyst, in particular titanium dioxide, to obtain ammonium methionate. Ammonia is released and discharged, and solid methionine is obtained as the final product. Despite the reaction temperature of the final step being 100°C, the conversion is not complete, and the publication is unable to draw any conclusions about the actual selectivity and yield of methionine in the reaction, resulting in undesirable residues of methionine amide remaining in the final product (Table 1, WO 2001 / 060788).

[0007] JP 03-093753 A discloses a method for hydrolyzing amino acid nitriles to amino acid amides or amino acids. The corresponding amino acid nitriles are hydrolyzed to methionine amides with at least 1 equivalent, preferably 10 equivalents, of water in the presence of 0.01-0.5 molar equivalents (mol equivalents) of a metal oxide from the group of zirconium oxide, titanium oxide, niobium oxide, titanium oxide tungsten oxide, titanium oxide tin oxide and titanium oxide zinc oxide at a temperature of 100-200°C. The subsequent hydrolysis step to methionine is carried out in the presence of a metal oxide from the group of zirconium oxide, titanium oxide, niobium oxide, titanium oxide tungsten oxide, titanium oxide tin oxide and titanium oxide zinc oxide. The yield of methionine with a zirconium oxide-titanium oxide-niobium oxide catalyst is at most 94% (Example 1, JP 03-093753 A). However, a drawback here is the relatively high demand for catalyst, i.e. 100 g of catalyst powder is required per 10 g of amino acid amide starting material (Example 1, JP 03-093753 A).

[0008] JP 03-093754 A also discloses a method for hydrolyzing an amino acid nitrile to an amino acid amide or an amino acid. The corresponding amino acid nitrile is hydrolyzed with at least 1 equivalent, preferably 10 equivalents, of water in the presence of 0.01-0.5 mol equivalents of a metal oxide selected from the group of titanium oxide-zirconium oxide, titanium oxide-aluminum oxide, titanium oxide-niobium oxide, titanium oxide-tungsten oxide, titanium oxide-tin oxide and titanium oxide-zinc oxide at a temperature of 50-220° C. The hydrolysis of the amino acid nitrile is carried out in the presence of 0.01-0.5 mol equivalents of a metal oxide selected from the group of titanium oxide-zirconium oxide, titanium oxide-aluminum oxide and titanium oxide-zinc oxide. However, according to Examples 5 and 1 (JP 03-093754 A), in the hydrolysis of methionine amide to methionine, the yield of methionine was only 93% (when using titanium dioxide zirconium oxide) and 94% (when using titanium dioxide niobium oxide), and the catalyst consumption was extremely high (0.34 g to 0.68 g of catalyst per 1 g of amide).

[0009] According to the above publications, mainly titanium dioxide-based catalysts have been used so far. The ZrO2 catalysts used in the discussed papers showed significantly poorer performance, and their crystal modification or structure-property relationships were not studied. It is also known that only titanium dioxide catalysts with the anatase crystal modification catalyze the reaction of methionine amide to methionine. On the other hand, TiO2 in the rutile modification does not show any catalytic effect.

[0010] EP 3199519 A1 discloses a method for preparing methionine by contacting 2-amino-4-(methylthio)butanenitrile and water with each other in the presence of a cerium-containing oxide catalyst. The cerium-containing catalyst is either a CeO2-based catalyst or a CeO2-ZrO2-based mixed oxide catalyst, each in the form of a fine powder. The yield of methionine ranges from 60.9% to 97.0%. According to the examples, the reaction is carried out at a temperature of 60 to 100°C and with a residence time of about 1 to 2 hours.

[0011] Furthermore, WO 2018 / 021338 discloses a method for preparing α-amino acids by reacting the corresponding α-amino acid amide with water in the presence of a zirconium compound and at least one other metal, such as hafnium or cerium. WO 2018 / 021338 discloses, inter alia, the hydrolysis of methionine amide to methionine using a zirconium-containing composite metal oxide catalyst containing Hf, Ce, Y or Ti (Examples 4, 5 and Comparative Examples 2, 3). However, the same publication does not disclose the ZrO2 content of the composite metal oxide catalyst, nor the particle size or other characteristics regarding the morphology of the catalyst. With regard to the continuous process, the same publication only discloses that continuous tank reactors and tubular reactors, also known as continuous stirred tank reactors (CSTRs) and plug flow reactors (PFRs), can be used. However, both are slurry reactors and are not suitable for large-scale processes such as methionine production due to their complicated operation. Nor do the examples provide a process that can be used for continuous production. This is because all of this is carried out in batches, for example in a steel pressure vessel with an inserted stirrer (Example 1).

[0012] Two more recent applications, WO 2020 / 161067 and WO 2020 / 161074, disclose further developments in the field of catalysts comprising CeO2 and ZrO2 for the hydrolysis of methionine nitrile to methionine.

[0013] WO 2020 / 161074 discloses a granular catalyst with a ZrO2 content of 60.0% to 99.5% by weight, which is stabilized by an oxide of hafnium and an oxide of at least one element M, where M is Ce, Si, Ti or Y, and has a median x50 of 0.8 mm to 9.0 mm. However, the catalyst can only be used for the hydrolysis of already formed methionine amide to methionine, but not for the complete hydrolysis of methionine nitrile to methionine starting from methionine nitrile. This makes the catalyst disadvantageous for methionine production.

[0014] WO 2020 / 161067 discloses a CeO2-based catalyst with a CeO2 content of 50% to 100% by weight for the direct production of methionine by hydrolysis of methionine nitrile, and a production process carried out with said catalyst. The catalyst is a nanopowder with a nanocrystallite size of 5 nm to 30 nm or 10 nm to 40 nm (minimum and maximum Feret diameter) and consists of agglomerates with a median of about 24 μm. However, for industrial applications, it is necessary to recover the catalyst at the end of the reaction, for example by filtration. In principle, the cross-flow filtration described in patent application WO 2020 / 161067 would be suitable for industrial applications. However, this approach requires high pumping capacities, which is disadvantageous for industrial implementation.

[0015] Classical and relatively cheap filtration techniques, such as strip filters or filter cartridges, are not practical, contrary to the examples in EP 3199519 and CN 112608261. This is because in aqueous solutions, the aggregates (median 24 μm) break down over time into smaller aggregates (median 0.4 μm) due to friction on the pipe walls and mechanical energy input by the pump used. The latter particle size range cannot be mapped by classical filtration. Extrusion of CeO2 nanopowder may be expected to be a suitable method for the preparation of shaped catalysts. However, Example 3.3 below shows that extruded catalysts (such as those produced by extrusion of CeO2 nanopowder in Example 2.1) result in low yields and low selectivities for the formation of methionine by hydrolysis of methionine nitrile. Thus, extruded catalysts are not suitable for use in the direct production of methionine by hydrolysis of methionine nitrile.

[0016] Thus, there remains a need for catalysts for the direct industrial-scale production of amino acids, such as methionine, by hydrolysis of aminonitriles, such as methionine nitrile, and / or aminoamides, such as methionine amide.

[0017] It has now been found that this problem is solved by preparing a CeO2-containing granular catalyst for the hydrolysis of aminonitriles and / or aminoamides to amino acids by high shear wet granulation of a CeO2-containing powder and at least one liquid binder, followed by drying and / or calcining the granules so obtained, and sieving the dried and / or calcined granules to a particle size of 100-5000 μm.

[0018] Thus, one object of the present invention is a method for preparing a CeO2-containing granular catalyst for the hydrolysis of aminonitriles and / or aminoamides to amino acids or derivatives thereof, comprising the steps of: a) subjecting a CeO2-containing powder and a liquid binder to high shear wet granulation to form a granulation; b) drying and / or calcining the granules obtained from step a); and c) sieving the dried and / or calcined granules obtained from step b) to a particle size of 100 to 5000 μm to obtain a CeO2-containing granular catalyst; The method includes:

[0019] In principle, any CeO2-containing powder can be used to prepare the granular catalyst according to the present invention, provided that the CeO2-containing powder has sufficient or desired catalytic activity in hydrolyzing aminonitriles, such as methionine nitrile and / or aminoamides, such as methionine amide, to the corresponding amino acids, such as methionine. For example, the CeO2-containing materials disclosed in EP 3199519, WO 2020 / 161067, or WO 2020 / 249495 can be used to prepare the granular catalyst according to the present invention.

[0020] In principle, the CeO2-containing powder is not subject to any restrictions on its size and shape, provided that the size and shape of the CeO2-containing powder are suitable for high shear wet granulation. The CeO2-containing powder is preferably a nanopowder.

[0021] In one embodiment of the method according to the invention, the CeO2-containing powder has a solubility of 35+ / -10% m as measured according to DIN ISO 9277-5 (2003). 2 / g~300+ / -10%m 2 / g BET surface area, both measured according to DIN ISO 9276-6 (2012) with an average maximum Feret diameter x of 3 + / - 10% nm to 40 + / - 10% nm Fmax,mean and the average minimum Feret diameter x of 2+ / -10%nm to 30+ / -10%nm Fmin,mean The CeO2-containing powder has

[0022] In a preferred embodiment of the method according to the invention, the CeO2-containing powder has a solubility of 35 + / - 10% m, measured according to DIN ISO 9277-5 (2003). 2 / g~65+ / -10%m 2 / g BET surface area, both measured according to DIN ISO 9276-6 (2012) from 10 + / - 10% nm to 40 + / - 10% nm average maximum Feret diameter x Fmax,mean and the average minimum Feret diameter x of 5+ / -10%nm to 30+ / -10%nm Fmin,mean The CeO2-containing powder has the following structure:

[0023] In another preferred embodiment of the method according to the invention, the CeO2-containing powder has a solubility of 175 + / - 10% m as measured according to DIN ISO 9277-5 (2003). 2 / g~300+ / -10%m 2 / g, or 225+ / -10%m 2 / g~265+ / -10%m 2 / g BET surface area, both measured according to DIN ISO 9276-6 (2012) with an average maximum Feret diameter x of 3 + / - 10% nm to 40 + / - 10% nmFmax,mean and the average minimum Feret diameter x of 2+ / -10%nm to 30+ / -10%nm Fmin,mean The CeO2-containing powder has the following structure:

[0024] The CeO2-containing powder preferably contains 50% to 100% by weight of CeO2. For example, the CeO2-containing particles contain 50%, 70%, 80% or 100% by weight of CeO2, with the remainder being one or more metals or metal oxides different from cerium or cerium oxide, such as ZrO2. The CeO2-containing particles may be a mixture of CeO2 with ZrO2 and / or TiO2, such as (CeO2) 0.5+x (ZrO2) 0.5-x For example, (CeO2) 0.5 -(ZrO2) 0.5 , (CeO2) 0.6 -(ZrO2) 0.4 , (CeO2) 0.7 -(ZrO2) 0.3 , (CeO2) 0.8 -(ZrO2) 0.2 Or (CeO2) 0.9 -(ZrO2) 0.1 , or (CeO2) 0.5+x (TiO2) 0.5-x , for example (CeO2) 0.5 -(TiO2) 0.5 , (CeO2) 0.6 -(TiO2) 0.4 , (CeO2) 0.7 -(TiO2) 0.3 , (CeO2) 0.8 -(TiO2) 0.2 Or (CeO2) 0.9 -(TiO2) 0.1 where x in each case is in the range from 0 to 0.5, for example 0, 0.1, 0.2, 0.3, 0.4 or 0.5. However, it is particularly preferred that the CeO2-containing particles contain 100% by weight of CeO2. In principle, it is also possible to use mixtures of CeO2-containing powders containing 100% by weight of CeO2 and CeO2, ZrO2 and / or TiO2, preferably CeO2 and ZrO2, in the method according to the invention.

[0025] Average minimum Feret diameter x of particles containing CeO2 Fmin,mean is always the average maximum Feret diameter of the particle x Fmax,mean It is preferable that it is smaller than .

[0026] The CeO2-containing particles have an average aspect ratio x of 0.55 to 0.85, measured according to DIN ISO 9276-6 (2012). Fmin,mean / x Fmax,mean It is preferred that the compound has the formula:

[0027] The CeO2-containing particles contain 50% to 100% by weight of CeO2 and have a 35m 2 / g~65m 2 / g and the average maximum Feret diameter x between 10 nm and 40 nm, both measured according to DIN ISO 9276-6 (2012) Fmax,mean and the average minimum Feret diameter x of 5 nm to 30 nm Fmin,mean , as well as an average aspect ratio x of 0.55 to 0.85 measured according to DIN ISO 9276-6 (2012) Fmin,mean / x Fmax,min It is even more preferred that the compound has the formula:

[0028] The CeO2-containing particles have an average aspect ratio x of 0.55 + / - 10% to 0.80 + / - 10% measured according to DIN ISO 9276-6 (2012) Fmin,mean / x Fmax,min It is preferred that the compound has the formula:

[0029] The CeO2-containing powder has a melting point of 175 + / - 10% m measured according to DIN ISO 9277-5 (2003). 2 / g~300+ / -10%m 2 / g, or 225+ / -10%m 2 / g~265+ / -10%m 2 / g BET surface area, both measured according to DIN ISO 9276-6 (2012) with an average maximum Feret diameter x of 3 + / - 10% nm to 40 + / - 10% nmFmax,mean and the average minimum Feret diameter x of 2+ / -10%nm to 30+ / -10%nm Fmin,mean , as well as an average aspect ratio x of 0.55 + / - 10% to 0.80 + / - 10% measured according to DIN ISO 9276-6 (2012) Fmin,mean / x Fmax,min It is further preferred that the ceramic material contains CeO2-containing particles having the following formula:

[0030] The CeO2-containing particles preferably have a lattice plane distance of 0.24±10% nm to 0.32±10% nm.

[0031] The CeO2-containing particles preferably include octahedral particles.

[0032] The CeO2-containing particles have a mean equivalent circular diameter x of 5 nm to 45 nm, measured according to DIN ISO 9276-6 (2012). A,mean It is preferred that the compound has the formula:

[0033] The CeO2-containing particles contain 50% to 100% by weight of CeO2 and have a 35m 2 / g~65m 2 / g and the average maximum Feret diameter x between 10 nm and 40 nm, both measured according to DIN ISO 9276-6 (2012) Fmax,mean and the average minimum Feret diameter x of 5 nm to 30 nm Fmin,mean , average aspect ratio x of 0.55 to 0.85 measured according to DIN ISO 9276-6 (2012) Fmin,mean / x Fmax,mean , as well as the average equivalent circular diameter x between 5 nm and 45 nm measured according to DIN ISO 9276-6 (2012) A,mean It is even more preferred that the compound has the formula:

[0034] The CeO2-containing particles have a mean equivalent circular diameter x of 3+ / -10% nm to 30+ / -10% nm, measured according to DIN ISO 9276-6 (2012). A、mean It is preferred that the compound has the formula:

[0035] The CeO2-containing powder has a melting point of 175 + / - 10% m measured according to DIN ISO 9277-5 (2003). 2 / g~300+ / -10%m 2 / g, or 225+ / -10%m 2 / g~265+ / -10%m 2 / g BET surface area, both measured according to DIN ISO 9276-6 (2012) with an average maximum Feret diameter x of 3 + / - 10% nm to 40 + / - 10% nm Fmax,mean and the average minimum Feret diameter x of 2+ / -10%nm to 30+ / -10%nm Fmin,mean , average aspect ratio x of 0.55 + / - 10% to 0.80 + / - 10% measured according to DIN ISO 9276-6 (2012) Fmin,mean / x Fmax,min , as well as the mean equivalent circular diameter x of 3 + / - 10% nm to 30 + / - 10% nm, measured according to DIN ISO 9276-6 (2012) A、mean It is further preferred that the ceramic material contains CeO2-containing particles having the following formula:

[0036] The CeO2-containing particles preferably have a crystallinity of at least 50%, and more preferably have a crystallinity of 50% to 100%, 50% to 95%, or 55% to 90%.

[0037] In the context of the present invention, the term high shear wet granulation is used as known to those skilled in the art and typically refers to a granular product development technique that includes (a) the addition and dry mixing of material powders, (b) the addition of liquid powder (either binder solution or solvent) to the powder mixture at lower impeller and chopper speeds, and (c) a wet massing step with both the impeller and chopper rotating at high speeds (which can be varied depending on the product).

[0038] In principle, the high shear wet granulation in step a) of the method according to the present invention can be carried out in any device suitable for granulation, as long as the CeO2-containing catalyst according to the present invention is obtained. The device used to carry out the high shear wet granulation in step a) is a typical high shear wet granulator, or a mixer or granulator suitable for this purpose. In principle, step a) of the method according to the present invention is not subject to any restrictions regarding the specific design of the high shear wet granulator, mixer or granulator used, as long as the CeO2-containing granular catalyst according to the present invention is obtained. For example, some high shear wet granulators are mainly composed of a mixing bowl, an impeller and an auxiliary chopper. The function of the impeller is to mix the powder and promote the densification of the granulation. The function of the chopper is to break up the wet mass or promote the growth of smaller particles. Other mixers or granulators suitable as high shear wet granulators include a mixing vessel with a rotating and tilting mixing pan, an eccentrically arranged mixing tool, and a scraper fixed to the wall or bottom. The eccentrically arranged mixing tool may be a pin-type rotor with several cylindrical or wedge-shaped pins extending along the rotation axis of the stirring tool. During stirring, the pins describe a circle coaxially surrounding the rotation axis. The use of such a stirring tool promotes the maintenance of a homogeneous liquid phase in the mixer. The powder is typically fed into the mixing vessel or mixing bowl of the granulator or mixer. The impeller or mixing vessel is then rotated at a given speed, for example in the range of 60 to 120 revolutions per minute, depending on the individual design of the mixer or granulator, while the chopper or mixing tool, preferably a pin-type rotor, is rotated in the opposite direction to the impeller or mixing vessel, for example with a circulation speed of 2 m / s to 10 m / s, for 60 to 120 seconds. The binder solution is added in portions, for example 85% first portion and 15% second portion, to the mixer or granulator through one or more nozzles for a total of 60 to 240 seconds while the circulation speed of the chopper or mixing tool is increased to 5 to 20 m / s. The walls of the vessel or bowl are then cleaned with a rubber wiper. The second portion of the binder solution is then added for 30 to 120 seconds at the same circulation speed of the chopper or mixing tool as for the first portion of the binder solution.The tank or bowl walls are then again washed with rubber wipers. The material thus obtained is granulated for 10 to 650 seconds at a chopper or mixing tool circulation speed of 20 to 60 m / s. The wet granulate thus obtained is then dried and / or calcined in step b).

[0039] In principle, the drying in step b) of the process according to the invention is not subject to any restrictions as to its implementation, in particular as to the time and temperature at which it is carried out, as long as these conditions allow drying the granulate obtained from step a) of the process. Nevertheless, it is preferred to carry out the drying of the granulate obtained from step a) at a temperature of at least 100° C., for example between 100° C. and 200° C., for at least 1 hour, for example between 1 hour and 5 hours.

[0040] Also, the calcination in step b) of the method according to the invention is in principle not subject to any restrictions with regard to its implementation, in particular with regard to the time and temperature under which it is carried out, as long as the granules obtained from step a) of the method are calcined under these conditions. The calcination in step b) is preferably carried out at a temperature in the range of 400°C to 900°C, in particular in the range of 400°C to 600°C, for a time range of 1 hour to 10 hours, preferably 3 hours to 8 hours. Calcination can be carried out with a temperature program with a predetermined heating rate, for example 5°C per minute, until a final temperature, for example 500°C, is reached. The final temperature is maintained for a defined time range, for example 5 hours, followed by cooling to room temperature within a defined time range, for example within 1 hour.

[0041] The sieving in step c) is not subject to any restrictions. The sieving of the granules to the target particle size range in step c) is preferably carried out using a suitable sieving machine. In particular, to obtain the granules in the target particle size range, two sieve bottoms having an upper mesh size and a lower mesh size are used. First, a sieve bottom having an upper mesh size, for example a mesh size of 1000 μm, is mounted on the sieving machine, and the part having a particle size larger than the desired size, here >1000 μm, is sieved. The granules that passed through the sieve are then subjected to a second sieving, this time using a sieve bottom having a lower mesh size, for example 500 μm. The sieve material retained on this sieve bottom is the target sieving fraction, here a fraction having a particle size of 500 μm to 1000 μm.

[0042] In a further embodiment of the process according to the invention, the dried and / or calcined granulate obtained from step b) is sieved in step c) to particle sizes of 125 μm to 500 μm, 500 μm to 1000 μm, 1000 μm to 2500 μm and / or 2500 μm to 5000 μm.

[0043] The fraction outside the target particle size range, e.g., <500 μm and >1000 μm, is sieved out in step c), but this does not mean that the granules are lost. Rather, it is preferred to send the granules, at least the larger ones, to a grinding step to obtain a CeO2-containing powder, which is then subjected to the process according to the invention again.

[0044] The CeO2-containing powder has a density of 0.05+ / -10% g / mL to 1.2+ / -10% g / mL. When the CeO2-containing powder is a mixture of a CeO2-containing powder containing 100% by weight of CeO2 and a CeO2-containing powder containing CeO2, ZrO2 and / or TiO2, the density is the density of the mixture.

[0045] In the context of the present invention, the term binder is used equivalently to the term binding agent and refers to a substance that holds other materials, here the CeO2-containing powder, together and forms a mechanically and chemically cohesive mass by adhesion or cohesion.

[0046] The liquid binder used in the method according to the invention comprises one or more binders and a granulation liquid. In principle, the at least one binder of the method according to the invention is not subject to any restrictions with respect to its composition and the number of components, e.g. specific binders and granulation liquids.

[0047] Thus, the liquid binder may comprise an inorganic binder and / or an organic binder. Good results have been obtained when the liquid binder comprises an organic binder, for example one or more organic binders, especially when the binder itself is an organic binder.

[0048] In one embodiment of the method according to the present invention, the liquid binder comprises an organic binder.

[0049] Suitable organic binders include natural polymers, synthetic polymers, or sugars, which act as adhesives to bind the powders together. Examples of natural polymers include sugars, such as polysaccharides available commercially as zusoplast PS1. Examples of synthetic polymers include polyvinyl alcohol available commercially as mowiol 8-88, polyvinylpyrrolidone available commercially as PVP K30, and cellulose ethers such as hydroxyethyl methylcellulose (HEMC), such as the various tyloses available commercially as Tylose MH1000.

[0050] During firing, the one or more organic binders burn off without leaving any residue and form the desired pores and surfaces in the grain structure.

[0051] The granulation liquid may be water or alcohol, which improves the solubility of all kinds of useful inorganic or organic binders. However, from the viewpoints of work safety and process simplicity, the granulation liquid is preferably water.

[0052] In another embodiment of the method according to the invention, the liquid binder contains water as the granulation liquid.

[0053] The method according to the invention opens the way to a specific catalyst for the hydrolysis of aminonitrile and / or aminoamide to the corresponding amino acid or its derivative on an industrial scale.

[0054] Therefore, another object of the present invention is obtained by the method according to the present invention, and / or - BET surface area of 70 + / - 10% m 2 / g ~ 130 + / - 10% m 2 / g measured in accordance with DIN ISO 9277-5 (2003), and - particle size of 100 μm to 5000 μm and A CeO2-containing granular catalyst for hydrolyzing aminonitrile and / or aminoamide to an amino acid or its derivative, having

[0055] In the context of the present invention, for the catalyst according to the present invention, a diameter d greater than 4 nm, i.e., 4 nm < d < 400 μm, is selected as representing the pore volume of macropores and mesopores, and a diameter smaller than 1 μm, i.e., 4 nm < d < 1 μm, is selected as representing the pore volume of smaller macropores and mesopores.

[0056] The catalyst according to the present invention preferably has a pore volume of 0.3 + / - 10% mL / g to 1.2 + / - 10% mL / g for 4 nm < d < 400 μm, and / or a pore volume of 0.1 + / - 10% mL / g to 0.7 + / - 10% mL / g for 4 nm < d < 1 μm.

[0057] In one embodiment, the catalyst according to the present invention has a particle size of 125 μm to 500 μm, 500 μm to 1000 μm, 1000 μm to 2500 μm and / or 2500 μm to 5000 μm.

[0058] The catalyst according to the invention preferably has a d50 value, measured according to ISO 13322-1:2004 and determined according to ISO 9276, of 400+ / -10% μm to 2000+ / -10% μm.

[0059] The catalyst according to the invention and the catalyst obtained by the method according to the invention are also characterized by a good mechanical stability. This is an exemplary comparison result of the particle size distribution of catalyst #3 according to the invention. The particle size distribution was determined before and after the use of said catalyst in a fixed bed reactor for the reaction of aminonitriles to a mixture containing the corresponding aminoamide and the corresponding amino acid, in which methionine nitriles to a mixture containing methionine amide and methionine (see example 3.4) were reacted for a total of 100 hours. Figure 2 shows the particle size distribution of catalyst #3 before and after use in the preparation of methionine for a total of 100 hours. No significant change is observed in the particle size distribution of catalyst #3 after use compared to the particle size distribution before the test. This shows that the catalyst particles are stable under the synthesis conditions applied in this test. In particular, this means that the catalyst according to the invention is also characterized by low attrition, preferably between 5 + / - 0.5% and 12 + / - 1%. The attrition of the catalyst is measured using a sieving machine, such as, for example, AS200 (Retsch GmbH) with a sieve bottom with a mesh size of 500 μm. For example, 10 g of the granulation already previously sieved is weighed out, placed on the sieve bottom and sieved in continuous operation at any set frequency for a given time, for example, 6 minutes at a frequency of 70 Hz. After sieving is completed, the sieve bottom is removed from the sieving machine and the final weight of the coarse material of the granulation retained on the sieve bottom with the abovementioned mesh size, here 500 μm mesh size, is determined. The attrition on a percentage basis is: Wear [%] = (10.00 gm (final weight) [g]) / 10.00 g It is calculated using the formula:

[0060] In one embodiment, the catalyst according to the invention has an attrition of 5+ / -0.5% to 12+ / -1%.

[0061] In another embodiment, the catalyst according to the present invention comprises 50% to 100% by weight of CeO2.

[0062] The bulk density of the catalyst according to the invention varies depending on its specific composition. For example, a catalyst containing 100 wt% CeO2 may have a bulk density in the range of 0.05 g / mL to 0.4 g / mL, preferably 0.1 g / mL to 0.2 g / mL. If the catalyst contains more than 50 wt% but less than 100 wt% CeO2, for example 30 wt% TiO2, 10 wt% or 15 wt% ZrO2, balance CeO2, the bulk density may vary from 0.05 g / mL to 2.0 g / mL, or from 0.1 g / mL to 1.5 g / mL, or from 1.0 g / mL to 1.5 g / mL. For particles, it is typical that the lower the bulk density, the higher the surface area of ​​the particle, and the higher the bulk density, the greater the mechanical stability of the particle. Both parameters typically have an opposite effect on each other. Therefore, in the case of the catalyst according to the present invention, at a bulk density of 0.05 g / mL to 2.0 g / mL, or 0.1 g / mL to 1.5 g / mL, or 1.0 g / mL to 1.5 g / mL, it is believed that there is a good balance between a large surface area of ​​the catalyst particles (typically achieved by a lower bulk density) and a high mechanical stability of the catalyst particles (typically achieved by a higher bulk density).

[0063] The catalyst according to the present invention preferably has a bulk density in the range of 0.05 to 2.0 mg / mL, preferably in the range of 0.1 to 1.5 g / mL.

[0064] The bulk density of the granular catalyst is measured using a measuring cylinder with a volume of 50 mL. The cylinder is placed on an analytical balance and the granulation obtained by sieving to the target particle size is poured in until a volume of 50 mL is reached, and then the final weight is read off the analytical balance. The bulk density of the material is calculated according to the formula: Bulk density [g / mL] = m (granulated material) [g] / 50 mL is obtained by

[0065] Both the catalyst obtainable by the process according to the invention and the catalyst according to the invention can be used in the hydrolysis of aminonitriles and / or aminoamides to amino acids.

[0066] A further object of the present invention is therefore a process for preparing an amino acid or a derivative thereof, comprising a step of contacting a solution or suspension containing an aminonitrile and / or an aminoamide with water in the presence of a catalyst obtained by the process of the invention and / or in the presence of a catalyst of the invention.

[0067] In the context of the present invention, the term amino acid is used as known to those skilled in the art to denote an organic compound having an amino group (-NH2) and a carboxyl group (-COOH) together with a side chain specific to each amino acid, the amino group being -NH3 + The carboxyl group can also exist in a protonated form as the carboxylate -COO - The term amino acid includes the D-enantiomers and L-enantiomers of the amino acid being discussed, as well as racemic mixtures of both enantiomers (often also referred to as the corresponding D,L-amino acid).

[0068] In the context of the present invention, the term amino acid derivative, or the use of the term derivative in relation to an amino acid, is used to indicate any analogue of the amino acid in question, in which the amino acid is replaced with a different functional group or moiety than the amino group, or in which a functional group in the side chain of the amino acid is replaced with a different functional group or moiety. For example, the amino group of methionine may be replaced with a hydroxy group in 2-hydroxy-4-(methylthio)butanoic acid, also known as methionine hydroxy analogue or methionine hydroxy analogue, abbreviated as MHA, or the hydroxy group of tyrosine may be replaced with a 4-hydroxy-3,5-diiodophenoxy moiety in thyroxine, 2-amino-3-[4-(4-hydroxy-3,5-diiodophenoxy)-3,5-diiodophenyl]propanoic acid. The term amino acid derivative also includes the D-enantiomer and L-enantiomer of the amino acid derivative of interest, as well as the racemic mixture of both enantiomers (often also referred to as the corresponding D,L-amino acid derivative).

[0069] In the context of the present invention, the terms aminonitrile and aminoamide are used to indicate the corresponding starting compound, which is hydrolyzed to obtain the desired amino acid or its derivative.For example, if the amino acid to be prepared is methionine, the corresponding aminonitrile is methioninenitrile, and the corresponding aminoamide is methionineamide.For example, if the amino acid derivative to be prepared is 2-hydroxy-4-(methylthio)butanoic acid, the corresponding aminonitrile is 2-hydroxy-4-(methylthio)butanenitrile, and the corresponding aminoamide is 2-hydroxy-4-(methylthio)butanamide.

[0070] The hydrolysis of an aminonitrile to the corresponding amino acid or its derivative always proceeds through the intermediate stage of the corresponding aminoamide. For example, if the hydrolysis reaction starts from methionine nitrile, it always proceeds through the intermediate stage of methionine amide, and finally obtains the desired methionine. Thus, the method according to the invention allows the preparation of an amino acid or its derivative starting from the corresponding aminonitrile, the corresponding aminoamide, or a mixture of both aminonitrile and aminoamide in any conceivable ratio. If it is intended to prepare a specific enantiomer of an amino acid or its derivative by the method according to the invention, it goes without saying that the hydrolysis starts from the specific enantiomer of the corresponding aminonitrile and / or aminoamide. For example, if L-methionine is prepared by the method according to the invention, the hydrolysis starts from L-2-amino-4-(methylthio)butanenitrile and / or L-2-amino-4-(methylthio)butanamide.

[0071] In principle, the method according to the present invention is not subject to any restrictions regarding the preparation of a particular amino acid or derivative thereof. Rather, any conceivable amino acid or derivative thereof can be prepared by the method according to the present invention, as long as the corresponding aminonitrile and / or aminoamide is available or usable. However, it is preferred to prepare an α-amino acid or derivative thereof by the method according to the present invention.

[0072] In the context of the present invention, the term α-amino acid is used as known to those skilled in the art and refers to amino acids that contain an amino group directly attached to the α-carbon, i.e., a carbon atom next to a carboxyl group. This term includes the secondary amines proline and hydroxyproline. Thus, α-amino acids are the most abundant amino acids in nature and the most relevant amino acids for human and animal nutrition and growth. Specifically, the 22 α-amino acids are called biogenic or proteinogenic amino acids because they are the building blocks of proteins. Thus, they are sometimes called essential amino acids.

[0073] In the context of the present invention, the use of the term α-amino acid derivative, or its derivative in the context of α-amino acids, is used to refer to any analogue of an α-amino acid in which the α-amino acid is replaced with a different functional group or moiety than the amino group, or in which a functional group in the side chain of the α-amino acid is replaced with a different functional group or moiety. For example, the amino group of methionine can be replaced with a hydroxy group in 2-hydroxy-4-(methylthio)butanoic acid, also known as methionine hydroxy analogue or methionine hydroxy analogue, abbreviated as MHA, or the hydroxy group of tyrosine can be replaced with a 4-hydroxy-3,5-diiodophenoxy moiety in thyroxine, 2-amino-3-[4-(4-hydroxy-3,5-diiodophenoxy)-3,5-diiodophenyl]propanoic acid. The term amino acid derivative also includes the D-enantiomer and L-enantiomer of the amino acid derivative under discussion, as well as the racemic mixture of both enantiomers (often also referred to as the corresponding D,L-amino acid derivative).

[0074] In one embodiment of the method according to the invention, the amino acid prepared is an α-amino acid or a derivative thereof.

[0075] In the context of the present invention, the terms α-aminonitrile and α-aminoamide are used to represent the corresponding starting compounds, which upon hydrolysis will give the desired α-amino acid or its derivatives. For example, if the α-amino acid to be prepared is methionine, the corresponding α-aminonitrile is 2-amino-4-(methylthio)butanenitrile (sometimes referred to herein as methionine nitrile, or MMP-AN), and the corresponding α-aminoamide is 2-amino-4-(methylthio)butanamide (sometimes referred to herein as Met-amide).

[0076] In principle, in the process according to the invention, any conceivable α-amino acid or its derivatives can be prepared from the corresponding α-aminonitriles and / or α-aminoamides. However, it is preferred that the α-amino acids prepared are methionine, lysine, threonine, tryptophan, valine or any derivatives thereof, since these are the α-amino acids of greatest commercial importance, at least from a nutritional point of view.

[0077] In one embodiment of the method according to the invention, the α-amino acid prepared is methionine, lysine, threonine, tryptophan, valine, or any derivative thereof.

[0078] The catalysts according to the invention and the catalysts obtainable by the process according to the invention are characterized by a good mechanical stability, so that their use in any type of reactor suitable for carrying out heterogeneous catalytic reactions is conceivable, for example a reactor with a fixed charge of the catalyst according to the invention, for example a fixed bed reactor, a reactor with a moving bed of said catalyst, i.e. a moving bed reactor, or a reactor with a fluidized bed of said catalyst, i.e. a fluidized bed reactor. However, it is preferable to carry out the process according to the invention in a fixed bed reactor, since the design of this reactor makes it possible to keep the mechanical stresses on the granular catalyst as low as possible.

[0079] The process according to the invention is preferably carried out in a fixed bed reactor.

[0080] In principle, the method according to the present invention is not subject to any restrictions regarding its design.Depending on the yield and selectivity for the production of the desired amino acid or its derivative, the method according to the present invention can be carried out in one run, two runs, or even multiple runs, and the reaction conditions of each run can be the same or different.In the case of two or multiple runs, the reaction output of one stage, for example the reaction output of the first stage, is the reaction input of the next stage, for example the reaction input of the second stage.

[0081] For example, it is advantageous to carry out the process according to the invention in two runs: in a first step, an aqueous solution of aminonitrile, for example methioninenitrile, is reacted in a fixed bed reactor, filled with a catalyst according to the invention and / or a catalyst obtained by the process according to the invention, to give a mixture of aminoamide, for example methionineamide, and amino acid or derivative thereof, for example methionine, and then in a second or further step, the resulting mixture is reacted in another fixed bed reactor, filled with a catalyst according to the invention and / or a catalyst obtained by the process according to the invention, to give the desired amino acid or derivative thereof. The first and second reactors, or further reactors, may be filled with the same catalyst, i.e. with a catalyst according to the invention having the same composition and / or the same properties. Preferably, the second or further step is carried out at a higher temperature than the first step, in order to achieve complete conversion of the starting material. It is preferred that the first step is carried out at a temperature up to 90° C., for example between 50° C. and 90° C., and the second or further step is carried out at a temperature up to 150° C., for example between 90° C. and 150° C. This makes it possible to obtain the desired amino acid or its derivative very efficiently.

[0082] The process according to the invention is preferably carried out at a temperature in the range of 50°C to 150°C, preferably 50°C to 90°C or 90°C to 150°C.

[0083] The method according to the invention is preferably carried out in two or more stages, in which case the reaction output of one stage, e.g. the reaction output of the first stage, is the reaction input of the next stage, e.g. the reaction input of the second stage.

[0084] It is further preferred that the process according to the invention is carried out in two or more stages, where the reaction output of one stage, e.g. the reaction output of the first stage, is the reaction input of the next stage, e.g. the reaction input of the second stage, and the next stage is carried out at a higher temperature than the temperature of the previous stage, e.g. 50°C-90°C, e.g. 90°C-150°C.

[0085] The space-time yield and the amount of catalyst used are important factors for industrial feasibility: with the granular catalyst according to the invention and with the granular catalyst obtained by the process according to the invention, the space-time yield is 0.05 h -1 ~10h -1 , preferably 0.2h -1 ~6h -1 Weight hourly space velocities (WHSV, i.e. mass of aminonitrile used per hour and mass of CeO2-containing granular catalyst) of 0.1 to 0.5 can be obtained, with simultaneous high conversions and high selectivities. The latter directly explains the activity of the granular catalyst, since an insufficient or reduced catalytic activity can lead to an increased residence time of the starting compounds, here for example aminonitriles. However, this favors the thermal decomposition of the starting materials, leading to side reactions such as the formation of dinitriles and secondary products, which in the worst case significantly reduces the yield and selectivity of the desired main acid or derivative.

[0086] Therefore, the method according to the present invention can be carried out in 0.05 h -1 ~10h -1 It is preferred that the reaction be carried out at a weight hourly space velocity of 1000 rpm or less.

[0087] The concentration of the aminonitrile in the method according to the present invention is preferably in the range of 5% to 20% by weight.

[0088] The pressure in the process according to the invention is preferably in the range from 1 bar to 10 bar.

[0089] The invention is further illustrated by the following examples and figures. [Brief description of the drawings]

[0090] [Figure 1] FIG. 1 is a graph showing the progress of conversion and yield. [Diagram 2] FIG. 2 shows particle size distribution of the catalyst before and after its use.

[0091] Description of the drawings Figure 1 shows the evolution of conversion and yield at T = 80 °C and WHSH = 0.6 h -1 The graph shows the results for Example 3.4, which was operated continuously for 96 hours at 100° C. The top black solid line (-) represents the conversion of 2-amino-4-(methylthio)butanenitrile (methionine nitrile, MMP-AN), the center black dashed line (-·-) represents the yield of 2-amino-4-(methylthio)butanamide (Met-amide), and the bottom dotted line (···) represents the yield of methionine (Met).

[0092] Figure 2 shows T=80℃, WHSH=0.6h -1 3 shows the particle size distribution before and after use of catalyst #3 in Example 3.4, which was operated at 40° C. for 100 hours. The black dashed line (--) represents the particle size distribution of catalyst #3 before use in testing, and the black solid line (-) represents the particle size distribution of catalyst #3 after use in testing for a total of 100 hours.

[0093] Working Example: 1. Analysis method 1.1 HPLC Chromatography: Chromatographic analysis of 2-hydroxy-4-(methylthio)butanenitrile (MMP-CN), 2-amino-4-(methylthio)butanenitrile (methioninenitrile, MMP-AN), 2-amino-4-(methylthio)butanamide (methionineamide, Met-amide), 3-(methylthio)propionaldehyde (MMP), and methionine (Met) was carried out using a JASCO or Agilent HPLC system with a RP-18 column (250x4,6mm; 5μm) followed by UV detection at 210nm. A mixture consisting of 3.3g H3PO4, 6.8g CH3CN and 89.9g HO was used as the eluent at a flow rate of 1mL / min. 10μL of each sample solution (50mg sample in 25mL HO) was injected into the eluent for analysis. Calibration was performed previously by injection of appropriate standard stock solutions of the analytes followed by comparison of peak areas with external standards, as is commonly done in organic chemical synthesis.

[0094] 1.2 BET surface area: BET surface area ABET It was measured by physically adsorbing nitrogen on the surface of the solid and calculating the amount of adsorbed gas corresponding to a monolayer on the surface in accordance with the Brunauer-Emmett-Teller (BET) method. Before measurement, the sample to be used (0.2 g to 0.9 g) was degassed at 150 °C for 20 minutes under vacuum. Then, the measurement was carried out at the temperature of liquid nitrogen (77 K). The amount of adsorbed gas was measured by three-point static volumetric measurement using a Tristar 3000 from Micromeritics Instrument Corporation. This method is generally described in DIN ISO 9277-5 (2003) and was applied in accordance with it.

[0095] 1.3 Measurement of pore volume and average pore diameter The pore volume and average pore diameter were measured in accordance with DIN 66134 (N2 sorption by Barret, Joyner, Halenda) for pore diameters in the range of 4 nm < d < 400 μm or 4 nm < d < 1 μm.

[0096] 1.4 Thermogravimetric analysis (TGA) Thermogravimetric analysis (TGA) was carried out in air at a heating rate of 5 K / min in the range of 25 to 500 °C.

[0097] 1.5 Particle size of granular catalyst The particle size of the granular catalyst was measured by optical analysis of 200 mL of each granular catalyst using a CCD camera of Camsizer® (Retsch Technology GmbH) in accordance with ISO 13322-1:2014, and the median d50 was measured in accordance with ISO 9276.

[0098] 1.6 Particle size distribution of powder The particle size distribution of the powders was determined by laser diffraction according to ISO 13320:2009 and the median d50 was determined according to ISO 9276. For this purpose, the material was mixed with 10 mL of water and 0.5 g / L of tetrasodium pyrophosphate and the mixture thus obtained was subjected to laser diffraction using a LS 13320 laser diffraction spectrometer (Beckmann-Coulter) equipped with a Universal Liquid Module (ULM).

[0099] 1.7 Sifting of granules to desired particle size range The granulation was sieved to the target particle size range using a sieving machine AS200DIGIT (Retsch GmbH). Two sieve bottoms, one with an upper mesh size and one with a lower mesh size, were used to obtain the granulation in the target particle size range. First, the sieve bottom with the upper mesh size, for example 1000 μm, was installed in the machine to sieve the part with a larger particle size than desired, here >1000 μm. The granulation that passed through the sieve was then subjected to a second sieve, this time using a sieve bottom with a lower mesh size, for example 500 μm. The sieve material retained on this sieve bottom is the target sieve fraction, here the fraction with a particle size between 500 μm and 1000 μm. The fraction outside the target particle size range, ie, <500 μm and >1000 μm, was re-milled and then used for further granulation.

[0100] 1.8 Measurement of Attrition and Bulk Density of Granular Catalysts The attrition of the granular catalyst was measured using a sieving machine AS200 (Retsch GmbH) with a sieve bottom with a mesh size of 500 μm. 10.00 g of the granulation, already pre-sieved, was placed on the sieve bottom and sieved in continuous operation for 6 minutes at a frequency of 70 Hz. After sieving was completed, the sieve bottom was removed from the sieving machine and the final weight of the coarse material of the granulation retained by the sieve bottom with a mesh size of 500 μm was measured. The attrition on a percentage basis was calculated according to the formula: Wear [%] = (10.00 gm (final weight) [g]) / 10.00 g was used to calculate.

[0101] The bulk density of the granular catalyst was measured using a measuring cylinder with a volume of 50 mL. The cylinder is placed on an analytical balance and the granulation obtained by sieving to the target particle size range is poured in until a volume of 50 mL is reached, and then the final weight is read off the analytical balance. The bulk density of the material is calculated according to the formula: Bulk density [g / mL] = m (granulated material) [g] / 50 mL is obtained by

[0102] 2. Preparation of catalytically active materials The CeO2 powder used for the preparation of the granular catalyst according to the present invention is characterized in its composition, crystallinity, lattice plane distance, BET surface area A BET , average maximum Feret diameter x Fmax,mean , average minimum Feret diameter x Fmin,mean , average aspect ratio x Fmin,mean / x Fmax,mean , and the mean equivalent circular diameter x A,mean With respect to the above, the present invention has the properties disclosed in European Patent Application Publication No. 3199519, International Patent Application Publication No. WO 2020 / 161067, or International Patent Application Publication No. WO 2020 / 249495.

[0103] Other chemicals used in the catalyst preparation, such as tylose MH 1000 (methylhydroxyethylcellulose), zusoplast PS1 (polysaccharide), mowiol 8-88 (polyvinyl alcohol) or PVP K30 (polyvinylpyrrolidone), were purchased from various vendors, such as Sigma Aldrich, and used without additional pretreatment.

[0104] 2.1 Extrusion of CeO2 nanopowder (not according to the present invention) 416.1 g of CeO2 nanopowder, 5 g of zusoplast PS1 (Zschimmer & Schwarz) and 15 g of tylose H 30000 P2 (Shin-Etsu Chemical) were fed into a universal kneader with a trough volume of 2.5 L (LUK 2.5) and premixed for 10 min with a kneader rotation speed of 40 revolutions per minute and a counter-acting discharge screw conveyor with a rotation speed of 11 revolutions per minute. The trough was cooled to a temperature of 10 °C in a cryostat. Subsequently, 50 g of demineralized water was added immediately after premixing, after a further minute and after a further minute of kneading time, and the rotation speed of the counter-acting discharge screw conveyor was increased to 25 revolutions per minute. After a further 2 minutes, 8.8 g of demineralized water was added and after a further 3 minutes, another 6.7 g of demineralized water was added again to adjust the plasticity of the kneaded product. The kneaded product showed good plastic deformability. Finally, 5 g of zusoplast WE8 (Zschimmer & Schwarz) was added after 8 min to adjust the wall slip of the kneaded material.

[0105] After 37 minutes of kneading under the above conditions, extrusion was started. For this, a nozzle with 4 x 2.7 mm perforations was used. The kneader rotation speed was set to 40 revolutions per minute, and the kneaded material was extruded from the nozzle by a screw conveyor, which is now operated at a rotation speed of 68 revolutions per minute ahead. Here, a pressure of 6.8 bar is set at the screw outlet. The extrudate coming out of the nozzle was cut into wire lengths of 4 mm + / - 0.5 mm in a wire granulator (rotation speed 400-600 revolutions per minute, number of wires 2).

[0106] The wet wire thus obtained was then pre-dried on a conveyor belt at 60° C. for 30 minutes and subsequently dried in air at room temperature overnight. The extrudates thus pre-dried were calcined in a muffle furnace (Nabertherm LT15 / 11 / P320) using a temperature program with a heating rate of 5° C. / min, a final temperature of 500° C. maintained for 5 hours, followed by cooling to 25° C. within 1 hour.

[0107] The resulting extrudates were 4 mm in length and 2.7 mm in diameter (catalyst #1). They were analyzed as described in Chapter 1 andBET = 27 m 2 / g, pore volume 4 nm < d < 400 μm [mL / g] = 2.26, pore volume 4 nm < d < 1 μm = 0.21, abrasion = 7.23%, bulk density = 1.5 g / mL were obtained.

[0108] 2.2 Granulation of CeO₂ nano powder according to the present invention 100 g of CeO₂ nano powder according to Table 1 was supplied to an Eirich laboratory mixer EL1 (Eirich Mischbehaelter 1L). The laboratory mixer was equipped with a pin-type rotor. The mixing tank was moved in the direction opposite to the rotation direction of the pin-type rotor in Step 1 (85 rotations per minute). Before adding the binder solution, the CeO₂ nano powder was mixed for 80 seconds at a circulation speed of 5 m / s of the pin-type rotor. Then, 85% of the amount of the aqueous binder solution listed in Table 1 was added within 140 seconds at a circulation speed of 10 m / s of the pin-type rotor. The wall of the tank was cleaned with a rubber wiper. Subsequently, the remaining 15% of the amount of the aqueous binder solution listed in Table 1 was added within 50 seconds at a circulation speed of 10 m / s of the pin-type rotor. Then, the wall of the tank was cleaned again with a rubber wiper. The material thus obtained was granulated at a circulation speed of 30 m / s of the pin-type rotor for the time described in Table 1.

[0109] The obtained wet granulated product was fired in a muffle furnace (Nabertherm LT15 / 11 / P320). A temperature program of heating at a rate of 5 °C / min, maintaining the final temperature of 500 °C for 5 hours, and then cooling to 25 °C within 1 hour was used.

[0110] Since the final weight was 96.1 g, the theoretical (yield) was 96.1%. The obtained granulated product was analyzed with an analytical sieve (Retsch) using a sieving machine AS 200 digit (Retsch). Fraction 1: > 2500 μm = 12.14 g = 12.63% Fraction 2: 1000 - 2500 μm = 43.08 g = 43% Fraction 3: 500 - 1000 μm = 24.25 g = 25.29% Fraction 4: 250 - 500 μm = 11.50 g = 11.93% Fraction 5: 125-250 μm = 4.52 g = 4.70% Fraction 6: <125 μm = 3.34 g = 2.41% The mixture was separated into sieved fractions.

[0111] [Table 1]

[0112] The target sieve fractions of 500–1000 μm and 1000–2500 μm were analyzed for their physical properties as described in Chapter 1 and the results are summarized in Table 2.

[0113] [Table 2]

[0114] 3. Synthesis Examples 3.1 Synthesis of 2-amino-4-(methylthio)butanenitrile starting from 2-hydroxy-4-(methylthio)butanenitrile 10.1 g of 2-hydroxy-4-(methylthio)butanenitrile (MMP-CN; 90 wt% in water, 69.3 mmol, 1 mol equiv.) was mixed with 26.0 g of NH3 (32 wt% in water, 7 mol equiv., 48.8 mmol) in a glass reactor, which was subsequently sealed. The slightly beige cloudy emulsion containing 25 wt% MMP-CN was stirred and heated to 50°C for 30 min using a preheated water bath. The resulting pale yellow solution was analyzed by HPLC chromatography, which confirmed 100% conversion of MMP-CN and 98.8% selectivity to 2-amino-4-(methylthio)butanenitrile (MMP-AN; 67.2 mmol) and 2-amino-4-(methylthio)butanamide (Met-amide; 1.2 mmol). The MMP-AN solution thus obtained consisted of 8.75 g MMP-AN (67.2 mmol), 0.18 g Met-amide (1.2 mmol), 7.14 g NH3 (419 mmol, 6 mol equivalents) and 19.9 g water.

[0115] 3.2 Direct conversion of the resulting 2-amino-4-(methylthio)butanenitrile to a mixture containing 2-amino-4-(methylthio)butanamide and methionine The MMP-AN solution obtained in Example 3.1 consisted of 8.75 g MMP-AN (67.2 mmol), 0.18 g Met-amide (1.2 mmol), 7.14 g NH3 (419 mmol, 6 mol equivalents) and 19.9 g water. An additional 36.2 g water was added to this solution to set the MMP-AN concentration to 12 wt% and was used in this example.

[0116] The conversion was carried out in a vertically installed fixed-bed reactor containing 3.0 g of various catalyst granules with a sieve fraction of 500-1000 μm obtained according to Example 2.2 and identified as catalysts used #2-#8 in Table 3 below. For this purpose, the reaction solution obtained according to Example 3.1 and having a MMP-AN concentration of 12% by weight was pumped into said fixed-bed reactor from above or below with a flow rate of 1.0 mL using a conventional double piston lift pump as typically used in HPLC equipment. This was carried out for 2.4 h. -1 This corresponds to a weight hourly space velocity of 1000 s. The fixed bed reactor was heated by electric jacket heating or double wall oil heating using a thermostat. The internal temperature was monitored using a PT100 thermocouple and the heating was set so that the temperature of the entire reaction was always kept constant at 70° C. The reactor was operated at ambient pressure. The internal diameter was 10 mm. The reactor was started with pure water and after reaching the operating temperature, the feed was switched to a solution containing 12 wt. % MMP-AN. After 2 hours of operating time, the reaction solution was collected for analysis using HPLC chromatography. The results are summarized in Table 3 below.

[0117] [Table 3]

[0118] 3.3 Direct conversion of 2-amino-4-(methylthio)butanenitrile to a mixture containing 2-amino-4-(methylthio)butanamide and methionine using granules of different particle sizes and at different weight hourly space velocities Granulated catalyst #2 was sieved into various particle size fractions as described in Section 2.2 and used as described below in Table 4. Extruded catalyst #1, prepared according to Section 2.1, was used as a comparative catalyst (see Table 4 below).

[0119] The catalyst was used in a fixed bed reactor as described in Example 3.2, and the reaction solution obtained from Example 3.1 was set to the desired MMP-AN concentration as shown in Table 4 by adding an appropriate amount of water. The fixed bed reactor loaded with catalyst of different sieve fractions or even extruded catalyst was operated at a pressure of 10 bar set by a pressure maintaining valve. The weight hourly space velocity and the internal temperature were adjusted as described in Table 4 below.

[0120] [Table 4]

[0121] 3.4 Direct conversion of 2-amino-4-(methylthio)butanenitrile to a mixture containing 2-amino-4-(methylthio)butanamide and methionine These experiments were performed at an internal temperature of 80°C and 0.6 h -1 The experiment was carried out in a fixed bed reactor as described in Example 3.2, using a solution containing 12 wt.% MMP-AN, except that the experiment was carried out at a WHSV of 1000 Hz for a total of 96 h. As the catalyst for the CeO2 catalyst granulation, catalyst #3 with a sieve fraction of 500-1000 μm according to Table 1 was used. The fixed bed reactor was operated at a pressure of 10 bar, set by the pressure-maintaining valve. After the experimental time listed in Table 5 below, the product solutions were separately collected and their compositions, from which the conversion of MMP-AN, the yield of Met-amide, the yield of Met and the selectivity to Met+Met-amide were determined and are summarized in Table 5 below. The evolution of the conversion and yield is shown in FIG. 1.

[0122] [Table 5]

[0123] After 100 hours of testing, the catalysts were analyzed for any potential changes in particle size distribution of catalyst #3. Figure 2 shows the particle size distribution of catalyst #3 before it was used in the test and after it was used in the test for a total of 100 hours. There is no significant change in the particle size distribution of catalyst #3 after it was used in the test for a total of 100 hours compared to its particle size distribution before the test. This indicates that the catalyst particles are stable under the synthesis conditions applied in this test.

[0124] 3.5 Reaction of the resulting solution containing 2-amino-4-(methylthio)butanenitrile and 2-amino-4-(methylthio)butanamide This experiment was performed using catalyst #2 as described in Example 3.2, with a reaction solution consisting of 0.7 wt% 2-amino-4-(methylthio)butanenitrile (MMP-AN), 6.8 wt% 2-amino-4-(methylthio)butanamide (Met-amide), 6.9 wt% methionine (Met), 10 wt% NH3, and 76.3 wt% water.

[0125] The solution was incubated at an internal temperature of 100°C and a WHSV of 0.25 h for a total test period of 78 h (see Table 6 below). -1 The reaction was carried out in a fixed bed reactor with catalyst #3 (see Table 1) according to Example 3.2, except that the reaction pressure was set at 0.25 bar. The reactor was operated at a pressure of 10 bar, set by a pressure maintaining valve. After the experimental time listed in Table 6 below, the product solutions were collected separately and their compositions, and from them the conversion of MMP-AN, the yield of Met-amide, the yield of Met and the selectivity to Met+Met-amide were determined, which are summarized in Table 6 below.

[0126] [Table 6]

Claims

1. CeO for hydrolysis of aminonitriles and / or aminoamides to amino acids or their derivatives 2 1. A method for preparing a particulate catalyst comprising the steps of: a) CeO 2 high shear wet granulation of the contained powder and liquid binder to form a granulation; b) drying and / or calcining the granules obtained from step a); and c) The dried and / or calcined granules obtained from step b) are sieved to a particle size of 100 to 5000 μm, and CeO 2 Obtaining a particulate catalyst containing A method comprising:

2. The CeO 2 The powder contains 50% to 100% by weight of CeO 2 35 + / - 10% m measured according to DIN ISO 9277-5 (2003) 2 / g~300+ / -10%m 2 / g BET surface area, average maximum Feret diameter x of 3 + / - 10% nm to 40 + / - 10% nm, both measured according to DIN ISO 9276-6 (2012) Fmax,mean and an average minimum Feret diameter x of 2 + / - 10% nm to 30 + / - 10% nm Fmin,mean 2. The method of claim 1, comprising:

3. The CeO 2 The powder content is 35 + / - 10% m measured according to DIN ISO 9277-5 (2003). 2 / g~65+ / -10%m 2 / g BET surface area, average maximum Feret diameter x of 10 + / - 10% nm to 40 + / - 10% nm, both measured according to DIN ISO 9276-6 (2012) Fmax,mean and an average minimum Feret diameter x of 5 + / - 10% nm to 30 + / - 10% nm Fmin,mean 3. The method of claim 2, comprising:

4. The CeO 2 The material contains a material with a viscosity of 175 + / - 10% m2 measured according to DIN ISO 9277-5 (2003). 2 / g~300+ / -10%m 2 / g, or 225 + / - 10% m 2 / g~265+ / -10%m 2 / g BET surface area, average maximum Feret diameter x of 3 + / - 10% nm to 40 + / - 10% nm, both measured according to DIN ISO 9276-6 (2012) Fmax,mean and an average minimum Feret diameter x of 2 + / - 10% nm to 30 + / - 10% nm Fmin,mean 3. The method of claim 2, comprising:

5. The CeO 2 The catalyst contains 50% to 100% by weight of CeO 2 The method according to any one of claims 1 to 4, comprising:

6. The method according to any one of claims 1 to 5, wherein in step c) the dried and / or calcined granulate obtained from step a) is sieved to a particle size of 125 μm to 500 μm, 500 μm to 1000 μm, 1000 μm to 2500 μm and / or 2500 μm to 5000 μm.

7. The method of claim 1 , wherein the liquid binder comprises an organic binder.

8. The method according to any one of claims 1 to 7, wherein the liquid binder comprises water as a granulating liquid.

9. 9. A CeO2 complex for hydrolysis of aminonitriles and / or aminoamides to amino acids or derivatives thereof, obtainable by the process according to any one of claims 1 to 8. 2 Contains particulate catalyst.

10. 10. The catalyst of claim 9, wherein the catalyst has a particle size of 125 μm to 500 μm, 500 μm to 1000 μm, 1000 μm to 2500 μm and / or 2500 μm to 5000 μm.

11. Catalyst according to claim 9 or 10, wherein the catalyst has a d50 value, measured according to ISO 13322-1:2004 and determined according to ISO 9276, of 400 + / - 10% μm to 2000 + / - 10% μm.

12. 12. The catalyst according to claim 9, wherein the catalyst has a pore volume of 4 nm<d<400 μm of 0.3+ / -10% mL / g to 1.2+ / -10% mL / g and / or a pore volume of 4 nm<d<1 μm of 0.1+ / -10% mL / g to 0.7+ / -10% mL / g.

13. The catalyst is 50% to 100% by weight of CeO 2 13. The catalyst according to any one of claims 9 to 12, comprising:

14. 14. A method for preparing an amino acid or a derivative thereof, comprising contacting a solution or suspension comprising an aminonitrile and / or an aminoamide with water in the presence of a catalyst obtained by a method according to any one of claims 1 to 8 and / or in the presence of a catalyst according to any one of claims 9 to 13.

15. The method of claim 14, wherein the amino acid prepared is an α-amino acid or a derivative thereof.